Higher-order chromatin structure in DSB induction, repair and misrepair - Falk, Martin; Lukášová, Emilie; Kozubek, Stanislav (Mutation research, 2010)
Double-strand breaks (DSBs), continuously introduced into DNA by cell metabolism, ionizing radiation and some chemicals, are the biologically most deleterious type of genome damage, and must be accurately repaired to protect genomic integrity, ensure cell survival, and prevent carcinogenesis. Although a huge amount of information has been published on the molecular basis and biological significance of DSB repair, our understanding of DSB repair and its spatiotemporal arrangement is still incomplete. In particular, the role of higher-order chromatin structure in DSB induction and repair, movement of DSBs and the mechanism giving rise to chromatin exchanges, and many other currently disputed questions are discussed in this review. Finally, a model explaining the formation of chromosome translocations is proposed.
Keywords: translokace genetická; chromatin; Models, Biological; oprava DNA; biologické modely; lidé; Radiation, Ionizing; Chromatin; ionizující záření; DNA Repair; DNA Damage; poškození DNA; Translocation, Genetic; Humans; dvouřetězcové zlomy DNA; DNA Breaks, Double-Stranded